Systematics of Amazonian lizards of the genus Potamites (Gymnophthalmidae) - Zurita Altamirano, Andrés Daniel (2015)
Although recent studies have helped unraveling the evolutionary history of the Neotropical lizard clade Gymnophthalmidae, many questions remain unanswered. Here we focus on assessing the diversity of the genus Potamites in Ecuador and Peru. Three mitochondrial and one nuclear marker of 172 individuals from both countries were combined to infer phylogenetic relationships among species of Potamites using Bayesian and Maximum likelihood methods. Our results demonstrate that Potamites is paraphyletic deriving in the misapplication of the name Potamites for the species P. cochranae and P. flavogularis which represent a tentative new genus. We also use bPTP species delimitation method to show cryptic diversity within P. ecpleopus and P. strangulatus, showing 30 unconfirmed candidate species (19 inside P. ecpleopus and 11 inside P. strangulatus). This could represent an increase in species richness inside each clade of 1900% and 1100% respectively.